A handbook for the assessment of children's behaviours with Wiley desktop edition - Williams, Jonathan 1959-; Hill, Peter (Chichester, West Sussex, [England] John Wiley & Sons, Ltd., 2012)
This ground-breaking book takes a new approach to the assessment of behaviour in children and adolescents. Written by an expert author team, combining one (JW) with higher qualifications in general practice, child neuropsychiatry, and child and adolescent psychiatry, with one (PH) with higher qualifications in medicine, paediatrics and child and adolescent psychiatry, the book draws on many thousands of multidisciplinary case discussions, at Great Ormond Street Hospital, in the Children's Multispecialty Assessment Clinic in North London, and in private practice.
Introduction -- Single symptoms -- Multiple symptoms occurring together -- Cognition -- General temporal patterns -- Motor (general) -- Motor (specific behaviours) -- Sensory -- Communication -- Social -- Home -- School -- Play -- Preferences (general) -- Preferences (specific) -- Breaking rules -- Anger -- Anxiety -- Negativeness -- Languor -- Digestive/excretory -- Bizarre experiences and ideas -- Contradictions.
"This book gives you access to a Wiley Desktop Edition - a digital, interactive version of your book available on your PC, Mac, laptop or Apple mobile device."--Page ii.
Includes bibliographical references (pages 577-616) and index.
Keywords: Behavioral assessment of children; Mental illness -- Diagnosis; Psychodiagnostics